Kollokationen in schriftlichen Textproduktionen. Eine empirische Untersuchung bei ungarischen DaF–Lernern - Pintye-Lukács, Erzsébet (Neofilolog, 2023)
The goal of this paper is to test productive collocational competence of German as a foreign language students at the University of Debrecen. The test aims to analyze compensational strategies that are used by students in their texts. In the first part of this paper we take a look at the terms collocation and collocational competence and the second part aims to show the results of the written test.